Harmonization among national cyber security and cybercrime response organizations: New challenges of cybercrime - Jang, Yunsik Jake (2013)
This paper will discuss the need for national-level organizational strategies to effectively combat cyber security threats and cybercrime. In many countries, new agencies have been established and/or new roles have been allotted to existing agencies to cope with the needs for cyber security or fighting against cybercrime. The two pillars of organizational structure and functions (i.e., security vs. law enforcement) have given new challenges to us, especially in the context of traditional criminal justice system. To illustrate the challenges, a case study examining the responses to major security incidents followed by nationwide debates and remarkable organizational changes in Korea will be given.Comment: 4th Asian Criminology Conference (2012